Gendered race: are infants’ face preferences guided by intersectionality of sex and race? - Kim, Hojin I.; Johnson, Kerri L.; Johnson, Scott P. (Frontiers in Psychology, 2015)
People occupy multiple social categories simultaneously (e.g., a White female), and this complex intersectionality affects fundamental aspects of social perception. Here, we examined the possibility that infant face processing may be susceptible to effects of intersectionality of sex and race. Three- and 10-month-old infants were shown a series of computer-generated face pairs (5 s each) that differed according to sex (F or M) or race (Asian, Black, or White). All possible combinations of face pairs were tested, and preferences were recorded with an eye tracker. Infants showed preferences for more feminine faces only when they were White, but we found no evidence that White or Asian faces were preferred even though they are relatively more feminized. These findings challenge the notions that infants’ social categories are processed independently of one another and that infants’ preferences for sex or race can be explained from mere exposure.